Przedsiębiorcy i ich sytuacja prawna w stanach nadzwyczajnych - Kocowski, Tadeusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
Extraordinary measures limit freedoms and rights of individual’s and entrepreneurs. Freedom of business activity can, however, be limited to alarger extent than constitutional freedoms and rights of individuals. So the situation of entrepreneurs is subject to greater restrictions than the situation of individuals.
Keywords: wolność gospodarcza; przedsiębiorcy; stany nadzwyczajne; obowiązki pracodawców; ograniczenie wolności gospodarczej